1967
DOI: 10.1063/1.1709570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mechanical and Thermal Treatment on the Structure and Magnetic Transitions in FeRh

Abstract: Well-annealed bulk samples of the intermetallic compound FeRh exhibit a first-order transition from antiferromagnetic to ferromagnetic order on heating near 330°K. Plastic deformation has been found to convert the normal CsCl-type ordered structure of FeRh to a disordered fcc structure, which is only weakly magnetic and does not exhibit the first-order transition. On annealing the disordered material at Ta=510°K, three stages of effects have been observed. In the first, the fcc phase converts to a highly order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
49
0
3

Year Published

1972
1972
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 3 publications
11
49
0
3
Order By: Relevance
“…4 However, the later can not explain the fact that the fch curve of the film stack evolves continuously as T increases above 100 K, with values lying well below the fcc curve (this up to temperatures near 220 K). As mentioned, the fcc and fch curves for pure Fe 3 Pt are much closer when compared to the large separation of the same curves in the film stack, evidencing the effect of the FeRh layer in the fch curve in the temperature region 100 K-220 K. The same effect seems to explain the reduction in the magnetisation of the zfc curve of the film stack relatively to the zfc curve of Fe 3 Pt (for Fe 3 Pt, the reduction in magnetization observed in the zfc curve below 230 K is a consequence of a misalignment of the domains, since as the temperature (or field) is increased the domains become more aligned). The zfc curve of the film stack, which lies well below the correspondent fch curve, also evolves continuously from 1.8 K up to 220 K. To better exemplify this discussion, it is plotted in the inset of Fig.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under supporting
confidence: 53%
See 3 more Smart Citations
“…4 However, the later can not explain the fact that the fch curve of the film stack evolves continuously as T increases above 100 K, with values lying well below the fcc curve (this up to temperatures near 220 K). As mentioned, the fcc and fch curves for pure Fe 3 Pt are much closer when compared to the large separation of the same curves in the film stack, evidencing the effect of the FeRh layer in the fch curve in the temperature region 100 K-220 K. The same effect seems to explain the reduction in the magnetisation of the zfc curve of the film stack relatively to the zfc curve of Fe 3 Pt (for Fe 3 Pt, the reduction in magnetization observed in the zfc curve below 230 K is a consequence of a misalignment of the domains, since as the temperature (or field) is increased the domains become more aligned). The zfc curve of the film stack, which lies well below the correspondent fch curve, also evolves continuously from 1.8 K up to 220 K. To better exemplify this discussion, it is plotted in the inset of Fig.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under supporting
confidence: 53%
“…The low angle diffraction curve was obtained about one year after 18 the diffraction curve presented in the inset of Fig. 1 was obtained and, besides the Fe 3 Pt peaks, it also shows a signal due to Fe 3 O 4 , which is absent in the diffraction curve show in the inset figure. This fact evidences that Fe 3 O 4 grew in the FeRh surface of the film.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%
See 2 more Smart Citations
“…[l] The transition to fcc structure was found rather earlier than the other stress-induced phase transition: It was first reported in 1960's by Lommel and Kouvel, who reported that fcc single phase powder was produced from B2 ordered FeRh alloys by filing at room temperature, and the same phase transition could be induced by cold rolling. [4] They observed the change in the magnetization of the stress induced fcc phase with temperature. The fcc phase was paramagnetic at room temperature, and metastable under 510K.…”
Section: Introductionmentioning
confidence: 99%